THE INFLUENCE OF LOCAL WISDOM ON SOIL FERTILITY IN SOUTH NIAS - Harefa, Darmawan (Universitas Nias Raya, 2024)
This study aims to explore the influence of local wisdom on soil fertility in South Nias. Local wisdom, which includes traditional agricultural practices such as the use of organic fertilizers, crop rotation, and sustainable forest management, has proven effective in enhancing soil quality and productivity. Through a literature review approach, data were collected from various sources to analyze the relationship between local practices and soil fertility. The results indicate that local wisdom not only improves soil fertility but also contributes to environmental preservation and ecosystem sustainability. These findings underscore the importance of integrating local wisdom into modern agricultural practices to achieve sustainable food security and community well-being in South Nias.